PEMBENTUKAN KOKRISTAL KETOKONAZOL-ASAM SUKSINAT YANG DIBUAT DENGAN METODE PENGGILINGAN (GRINDING) - Yuli Ainun Najih; Dwi Setyawan; Achmad Radjaram (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
The Co-crsytal formation ketoconazole (KTZ) - succinic acid (SA) has been performed by molar ratio (1:1) using milling method (grinding).. Milling is done using Planetary Ball mill PM 200 MA-type tool, Retsch with 75 rpm milling speed. The physical mixture of KTZ and AS molar ratio (1:1) was prepared in the absence of a dry grinding solution with milling time of 5, 15, 30, 45 and 60 min at a constant velocity. The milling results are seen by using powder X-ray diffraction (PXRD) at an angle (2Î¸ = 7.8o). From the results of X-ray powder diffraction there is an increase in the percentage of crystalline (% w/w). The result of the grinding time curve with the percentage of crystal (%w/w), the result that the percentage of crystalline (% w/w) increases linearly with increasing milling time (min) based on the maximum intensity data of each milling time by the line equation (y = 0.690x + 51.09) and correlation coefficient r = 0.9905. As conclusion, based on kinetic formation of cocristal with milling method obtained for slope value = 0,690 % cocrystall (%b/b)/min.